(3fRgI GdGdHGH hZQGFH GdGZJQGH aj GdPgGH hGdGbGeI hGdGjGHs - (3GdMSjfj GdBdhSj, CHh GdKfGA, TgGH GdOjf, eMehO Hf YHO Gddg Hf eMehO Hf OQhjT, J (B1270 (3g`s
(3ChdgG (B:s
(3GdMeO ddg aEfj NQLJ ef RhGjG GdRhQGA efgLG Cbhe WQjb eMehdG ef aVd Gddg JYdi Ydi eWGjG GdfYeGA HCjOj Qajb GdJhajb hPdc aj ZQI LeGOi SJI ef SfI SHY hSJjf ef GdbQf GdKGdK YTQ HYO gLQI SjO bQhf GdChdjf s
(3BNQgG (B:s
(3hddCOjH GdMGL LhGO GdTgjQ HHPcJ GdcQHdGFj hgh bhdg (B: (3dG QjH aj gPG GdcJGH deG Hg (B, (3ef hUd WdGH HaUd NWGH(B,, (3eGPG Cahg ef GdKfG hCHh GdKfG (B, (3bO aGg ajg HMceI hUhGH Jes
(3Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\176s
(3EjVGM Gdecfhf (B2\143s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdLZQGajG hGdHdOGfs